Reading Chuck Palahniuk American monsters and literary mayhem - Kuhn, Cynthia 1965-; Rubin, Lance (Routledge, 2012)
This collection examines how Chuck Palahniuk pushes through a variety of boundaries to shape fiction and to interrogate American cultures in powerful and important ways. His innovative stylistic accomplishments and notoriously disturbing subject matters invite close analysis, and these new essays insightfully discuss Palahniuk's texts, contexts, contributions, and controversies. Addressing the novels from Fight Club through Snuff , as well as his nonfiction, this volume will be valuable to anyone with a serious interest in contemporary literature
Keywords: Palahniuk, Chuck -- 1962-; Aufsatzsammlung